Preparation of Saussurea costus Traditional Oil and Investigation of Different Parameters for Standardization - Sahar Bagheri; Nastaran Ebadi; Zahra Taghipour; Azadeh Manayi; Tayebeh Toliyat; Mehran Mirabzadeh Ardakani* (Iranian Society of Pharmacognosy, 2018)
Background and objective: Medicinal oils are one of the most common and special dosage forms in oral and topical therapies of Persian medicine (PM). The oil of Saussurea costus (bitter qust) root is prominent topical oil with different applications in PM. In this study, the oil of bitter qust was prepared according to ancient Persian medical texts. Methods: To prepare traditional qust oil, 100 g of the root was soaked in 600 mL aqueous ethanol 25% overnight. The supernatant was then filtered and boiled in 800 g sesame oil until all water was evaporated. The essential oil of the root and volatile components of its traditional oil were extracted using hydro-distillation method in a Clevenger-type apparatus and were analyzed by gas chromatography-mass spectrometry (GC-MS) method. Total phenolics, flavonoids, tannins and polysaccharides were determined by spectrophotometric methods to evaluate the chemical parameters of traditional bitter qust oil.  Results: The content of volatile compounds in both investigated samples was determined (0.5% and 0.1% (v/w), respectively). Dehydrocostus lactone and 1, 3-cyclooctadiene were two similar main compounds in the both analyzed samples. Total phenolics (788.290±0.61 mg/L gallic acid equivalent (GAE)), flavonoids (303.2±2.52 mg/L catechin equivalent (CE)), tannins (23.97±0.52 mg/L GAE) and polysaccharides (9.240±0.13 mg/L dextrose equivalent (DE)) contents were determined. Conclusion: According to the obtained data, dehydrocostus lactone could be used for determination and evaluation of traditional bitter qust   oil.